2002
DOI: 10.1172/jci15640
|View full text |Cite
|
Sign up to set email alerts
|

Immune complex–mediated antigen presentation induces tumor immunity

Abstract: Antigen uptake receptors on dendritic cells (DCs) provide efficient entry for the initiation of antigen-specific adaptive immunity. Here we show that targeting of antigen to Fc receptors on DCs accomplishes combined activation of Th1 CD4 and CD8 effector responses in vivo, namely delayedtype hypersensitivity and tumor immunity. Tumor immunity specific for ovalbumin-expressing tumors was provided by immunization with wild-type but not FcγRγ -/-DCs loaded with ovalbumincontaining immune complexes. Tumor protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
100
2
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(109 citation statements)
references
References 43 publications
6
100
2
1
Order By: Relevance
“…This finding is in line with an observation (in bone marrow-derived dendritic cells) showing that in contrast to Fc␥RIII-mediated uptake of ICs, which leads to rapid delivery of the internalized IC to lysosomes, delivery of ICs to lysosomes is delayed after internalization by Fc␥RIIb, resulting in intracellular accumulation of undegraded ICs. 44 However, whether this also holds true for the in vivo situation is unclear, although studies in Kupffer cell-depleted rats, showing that the rate of degradation of aggregated IgG by LSECs is lower than that in normal animals, 45 suggest that endocytic processes similar to those observed in vitro also may occur in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with an observation (in bone marrow-derived dendritic cells) showing that in contrast to Fc␥RIII-mediated uptake of ICs, which leads to rapid delivery of the internalized IC to lysosomes, delivery of ICs to lysosomes is delayed after internalization by Fc␥RIIb, resulting in intracellular accumulation of undegraded ICs. 44 However, whether this also holds true for the in vivo situation is unclear, although studies in Kupffer cell-depleted rats, showing that the rate of degradation of aggregated IgG by LSECs is lower than that in normal animals, 45 suggest that endocytic processes similar to those observed in vitro also may occur in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…ICs loaded on DCs could induce in vivo CD4 ϩ and CD8 ϩ CTL responses and mediate full tumor protection (30,37) correlated with induction of DC maturation. Syk-deficient DCs could not signal through the ␥-chain-dependent activating Fc␥Rs (type I and III), but Fc␥RIIB signaling (i.e., the recruitment of SHIP phosphatase; Ref.…”
Section: Discussionmentioning
confidence: 99%
“…A predominant inhibitory effect of Fc␥RIIB on tumor immunity and DC maturation has been suggested to induce tolerogenic DCs (36). However, another study showed that Fc␥R engagement in DCs Fc␥RI/II/III ϩ induces maturation and protective antitumor immune responses (37). These different studies have used DCs generated in vitro using slightly different protocols, which may account for the observed discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…The balance of activating versus inhibitory FcγRs may also be altered by cytokines, thereby regulating FcγR mediated cross presentation [44]. In mice genetically lacking inhibitory FcγRIIB, targeting immune complexes to DCs can lead to enhanced generation of antigen specific CD8+ T cell immunity in vitro and in vivo [45,46]. Likewise, genetic deletion of FcγRIIB leads to spontaneous autoimmunity in genetically prone mice [47].…”
Section: Role Of Fcγr Balance In Adaptive Immunitymentioning
confidence: 99%